Detection of direct oral anticoagulants with the dilute Russels viper venom time – observations in a real life setting. (14th October 2021) - Kloeter, T; Siegemund, T; Siegemund, A; Laufs, U; Petros, S; Metze, M
Abstract: Background: The detection of direct oral anticoagulants (DOACs) in emergency settings still remains challenging, especially when dedicated anti-Xa or anti-IIa tests are not readily available or the specific DOAC is unknown. The dilute Russel's viper venom time (dRVVT) is widely known in lupus anticoagulant (LA) testing and may also provide helpful information regarding the residual antithrombotic activity of DOACs. Yet real world data describing the effect of DOACs on the dRVVT is scarce. Objective: The study aimed to evaluate the sensitivity and specificity of dRVVT for different DOAC plasma levels. Methods: A total of 80 patients were recruited – 20 patients for each approved DOAC (apixaban, edoxaban, rivaroxaban and dabigatran). Blood plasma was sampled before (baseline), 6 and 12 hours after DOAC-intake and at plasma peak time. DRVVT was measured using the LA1 screening assay for lupus anticoagulant. Plasma levels were measured by calibrated anti-Xa or anti-IIa tests. Additionally, activated partial thromboplastin time (aPTT) and prothrombin time (PT) were measured. Results: All DOACs significantly prolonged the dRVVT. The effects were more pronounced at higher DOAC plasma levels. The area under the receiver operating characteristic (ROC) curve regarding a plasma level cut-off of 30 ng/ml was 0.92 (95% confidence interval (CI) 0.823 to 1.00) for apixaban, 0.97 (95% CI 0.902 to 1.00) for edoxaban, 0.87 (95% CI 0.649 to 1.00) for rivaroxaban and 0.96 (95% CI 0.871 to 1.00) for dabigatran. Conclusion: A dose dependent effect of all approved direct oral anticoagulants (DOACs) on the dilute Russel's viper venom time (dRVVT) was documented in our real world setting, while relevant DOAC plasma levels did not affect standard coagulation tests. The negative predictive value for the dRVVT was high even at low DOAC plasma levels. The dRVVT could therefore be helpful to rule out relevant antithrombotic plasma activity caused of DOACs in emergency situations. FUNDunding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Universität Leipzig